(untitled) (Philological Studies: Scientific Bulletin of Kryvyi Rih State Pedagogical University, 2012)
In this article aspects of language and cultural interaction are examined; main principles of linguistic and cultural approach in phraseology are formulated; place and role of intertextual phraseologisms in the language world picture are determined.